P Bodies Inhibit Retrotransposition of Endogenous Intracisternal A Particles - Lu, Chunye (American Society for Microbiology, 2011)
mRNA-processing bodies (P bodies) are cytoplasmic foci that contain translationally repressed mRNA. Since they are important for the retrotransposition of Ty elements and brome mosaic virus in yeast cells, we assessed the role of P bodies in the movement of endogenous intracisternal A particles (IAPs) in mammalian cells. In contrast to the case for these other systems, their disruption via knockdown of RCK or eukaryotic initiation factor E transporter (eIF4E-T) increased IAP retrotransposition as well as levels of IAP transcripts, Gag proteins, and reverse transcription products. This increase was not mediated by impairing the microRNA pathway. Rather, the removal of P bodies shifted IAP mRNA from nonpolysomal to polysomal fractions. Although IAP mRNA localized to P bodies, Gag was targeted to the endoplasmic reticulum (ER), from which IAP buds. Thus, by sequestering IAP mRNA away from Gag, P bodies inhibit rather than promote IAP retrotransposition.